Unsteady Flow Mechanisms of the Stability Improvement for an Optimized Compressor - T. Zhou; Z. X. Liu; X. J. Li; M. Zhao; Y. J. Zhao; L. C. Xu (Journal of Applied Fluid Mechanics)
Radial compressor is a crucial component of turbocharging systems in aviation engines. Enhancing flow stability of radial compressor contributes to performances improvement of engines. Ported shroud (P-S) casing-treatment can effectively broaden the compressors flow stability range. However, the unsteady mechanisms of the P-S are still unclear. In this study, a collaborative optimization of the P-S and the impeller-diffuser is firstly carried out. The results show that the optimized compressor exhibits higher efficiency and larger flow stability range than the original and the solid-casing compressors. Then, the unsteady mechanisms of the flow stability enhancement for the optimized compressor are analyzed by the dynamic-mode-decomposition (DMD) method. It is found that the decrease of the energy proportion of the inherent mode and the increase of the low-frequency multi-scale modes are correlated to the flow instability of the compressor. The increased recirculating flow rate of the optimized compressor has removed more tip leakage flow (TLF) and double leakage flow (DLF) in the impeller inducer shroud, and then reduces the interplay among the TLF, the DLF and the leading-edge (LE) shock wave. Therefore, the generation of low-frequency multi-scale modes is suppressed, while the inherent modes are intensified. Consequently, the flow stability of the compressor is enhanced. This study may offer a new approach to enhance compressor stability by adjusting the energy proportions of inherent modes and low-frequency multi-scale modes.